Imagination and Creativity: Cultural–Historical Approach - Kravtsov G.G.; Kravtsova E.E. (Психолого-педагогические исследования)
Consideration of the concept of imagination in the context of cultural-historical psychology led to the conclusion that there are two differently directed processes. One process involves making sense of things in the outside world and the present situation, that is, it means understanding and rethinking external objects and situations. Another process involves the construction of a new image that allows you to see and understand the surrounding reality in a new way. This allows the authors to say that, on the one hand, imagination is aimed at acting with external reality, and, on the other hand, the inner work of creating a new subject of imagination. Based on the analysis of empirical materials studying the development of imagination and creativity, the authors obtained experimental proof of the idea of L.S. Vygotsky that images of imagination are realized in creativity and come to the conclusion about the possibility of purposeful development of creativity in ontogenesis. Authors connect the purposeful development of creativity with theatrical pedagogy, in which training and education are realized with the help of theatrical methods. Theatrical methods, according to the authors, are methods by which you can set an imaginary situation and, at the same time, these are methods that allow the viewer to be included in theatrical action.